Severe Ovarian Hyperstimulation Syndrome Complicated by Suspected Sepsis: A Case Report - Prastika Candra Triastuti; Imam Nafi Yana Saputra; Anthony Anthony; Kevin Zufaries Fary; Arifah Pelangi Nusa; Muhammad Alamsyah Aziz; Edy Priyanto (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Introduction: Ovarian hyperstimulation syndrome (OHSS) is a serious complication of ovulation induction for infertility treatment. This case report discusses severe OHSS complicated by suspected sepsis. This report aims to remind healthcare professionals about the best management options for severe OHSS cases. Case Report: Case report of severe OHSS with a normal 4-week 1-day gestation in a 26-year-old primigravida who presented in our emergency room as a result of 6 days of abdominal pain and an enlarged abdomen progressively aggravated for 5 days, with a SOFA score of 3. The patient’s vital signs indicated shock. She was admitted to the ICU for 4 days. She has significant risk factors: a history of IVF and the development of polycystic ovary syndrome (PCOS). On ultrasound imaging, we found ascites and multiple follicles with no gestational sac. A diagnosis of severe ovarian hyperstimulation was made.Conclusion: Severe and critical forms of OHSS are potentially lethal disorders. Although OHSS is potentially life-threatening, its clinical detection is often delayed. Proactive strategies should be encouraged and enhanced to avoid severe complications. Our case report reminds to understand the signs, symptoms, and management of severe OHSS.Penatalaksanaan Sindrom Hiperstimulasi Ovarium Berat dengan Syok Sepsis sebagai Komplikasi: Laporan KasusAbstrakPendahuluan: Sindrom hiperstimulasi ovarium (OHSS) merupakan komplikasi serius dari induksi ovulasi dalam pengobatan infertilitas. Laporan kasus ini membahas HSS berat yang diperberat dengan dugaan sepsis. Tujuan laporan ini untuk mengingatkan tenaga medis tentang pilihan penatalaksanaan terbaik pada kasus OHSS berat.Laporan Kasus : Penelitian ini melaporkan sebuah kasus OHSS berat dengan kehamilan normal usia 4 minggu 1 hari pada seorang primigravida berusia 26 tahun yang datang ke unit gawat darurat dengan keluhan nyeri perut selama 6 hari, pembesaran perut yang semakin memburuk selama 5 hari, dan skor SOFA 3. Tanda vital pasien menunjukkan syok. Pasien dirawat di ICU selama 4 hari. Pasien memiliki faktor risiko yang signifikan, yaitu riwayat program bayi tabung (IVF) dan menderita sindrom ovarium polikistik (PCOS). Pada pemeriksaan ultrasonografi ditemukan asites dan folikel-folikel multipel tanpa kantung gestasi. Diagnosis sindrom hiperstimulasi ovarium berat pun ditegakkan.Kesimpulan: OHSS berat dan kritis merupakan kondisi yang berpotensi mengancam jiwa, namun deteksi klinisnya sering terlambat. Strategi proaktif harus didorong dan ditingkatkan untuk menghindari komplikasi yang berat. Laporan kasus kami mengingatkan untuk memahami tanda, gejala, dan penatalaksanaan OHSS berat.